The JPEX scandal: a test case for Hong Kong’s new cryptocurrency regulatory regime or is it still the wild west? - Noble Po Kan Lo; Noble Po Kan Lo; Tony Hon Yiu Lau; Tony Hon Yiu Lau (Frontiers in Blockchain)
This paper investigates the challenges and effectiveness of Hong Kong’s regulatory framework for digital assets and cryptocurrencies in the wake of the JPEX Scandal. The scandal serves as the first significant test of the city’s regulatory measures aimed at protecting consumers and investors from fraudulent activities within the crypto space. The study delves into the background and development of blockchain technology and cryptocurrencies, highlighting their rapid evolution and the associated regulatory challenges. By examining the JPEX case, the paper evaluates the robustness of Hong Kong’s regulatory tools and their ability to balance consumer protection with fostering innovation. The paper employs a doctrinal legal methodology, supplemented by a case study of JPEX, to assess whether the current regulatory framework is adequate or if further adjustments are required. The findings suggest that while significant strides have been made, certain gaps remain, particularly concerning decentralised finance (DeFi) and decentralised autonomous organisations (DAOs). The paper concludes with recommendations for enhancing regulatory clarity and ensuring the sustainable growth of Hong Kong as a global crypto hub.